Air's affinities: Geopolitics, chemical affect and the force of the elemental. (March 2015) - Adey, Peter
In the midst of renewed geographical and geophilosophical interest in the Earth, the biosphere and, specifically, what has been called an 'aerography', this article explores how air might be made sense of as elemental. As a different way to apprehend elements to notions within the turn to a material–affective thing–power, assemblage theory or geophysical processes and complexities, the article explores air by apprehending it through chemical–alchemic notions of affinity and a political–mythic philosophical elementalism. In so doing, it is suggested that we might bring the air to account rather differently.